Comment on“The Keisarhjelmen detachment records Silurian–Devonian extensional collapse in Northern Svalbard” - Dallmann, Winfried; Piepjohn, Karsten (Terra Nova, 2018)
This is the peer reviewed version of the following article: Dallmann, W. & Piepjohn, K. (2018). Comment on “The Keisarhjelmen detachment records Silurian–Devonian extensional collapse in Northern Svalbard”. Terra Nova . 30(4), 319-321, which has been published in final form at https://doi.org/10.1111/ter.12335 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Introduction : The discussed area has been investigated since the 1960s. Scientists of the Norwegian Polar Institute, the Cambridge scholar environment, the University of Münster and others have mapped, described, interpreted and contributed to the discussion through decades. Very little of this is reflected in the paper by Braathen, Osmundsen, Maher, and Ganerød, (2018). A discussion of previous models is absent. We appreciate the introduction of a new model inspired by the authors’ knowledge of Devonian basins in southern Norway and other places. It may certainly contribute new aspects. We react, however, to the way these new aspects are presented, claiming to fundamentally replace earlier models, without a thorough documentation and without discussing the wealth of previously available data.